Sistem Pakar Mendiagnosa Penyakit Kaki Gajah Menggunakan Metode Certainty Factor - Nelly Astuti Hasibuan; Hery Sunandar; Senanti Alas; Suginam Suginam (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2017)
Elephant foot disease or filariasis is a contagious disease caused by filarial worms that are transmitted through the type of mosquito. This disease is chronic and if not get treatment will result in permanent disability in the form of leg enlargement, genitals both women and men. Elephant foot disease is generally detected through blood microcopy examination. Until now it is still felt because microfilaria only appear in the blood at night for several hours (nocturnal perioicity). In addition, various methods of examination are also performed to diagnose elephantiasis diseases such as those known as membrane crawl, knott concentration method and deposition technique. This study identifies elephantiasis and its causes, and applies certainty factor methods and designs expert systems to diagnose elephantiasis. To diagnose elephantiasis by using certainty factor method. Patients will be given questions to obtain probable values and then the values obtained will be solved by certainty factor formulation, so that the diagnosis and percentage is likely to develop elephantiasis.